Cross-border concentrated solar power projects - opportunity or dead end? A study into actor views in Europe. (April 2022) - Burghard, Uta; Dütschke, Elisabeth; Caldes, Natalia; Oltra, Christian
Abstract: Cross-border renewable energy projects (in particular those based on concentrated solar power (CSP)) could play an important role in the future EU energy systems. Be it by contributing to enhanced energy security, improving the management of the energy system or meeting the EU renewable energy target in a cost-effective manner. However, despite the expected benefits associated with the use of cooperation mechanisms set up under the Renewable Energy Directive, several barriers and, possibly, lack of active support have prevented a wide use of these mechanisms among Member States. This paper explores whether social acceptance, or lack thereof, can explain some of this lag in development. Collecting actor views on CSP cooperation mechanisms between EU Member States forms the basis of this analysis. The empirical basis consists of 43 interviews from Spain as a potential host for and Germany and the Netherlands as potential consumers of renewable energy (off-taker countries). The data analysis outlines that overall CSP cooperation mechanisms are seen positively; however, the complexity of implementation, heterogeneity of actor views, as well as high costs for CSP are perceived as downsides. Thus, overall, a societal impetus is missing and interest in further development seems limited. Highlights: Development of concentrated solar power (CSP) has been slow in Europe. Cooperation mechanisms have the potential to change that but have rarely been used. We present an analysis based on interviews from Spain, the Netherlands and Germany. Perceptions for CSP and also for cooperation mechanisms are overall positive. Some actor groups lack knowledge and awareness. A guiding narrative is missing.